Hubungan Kinerja Lingkungan dan Pengungkapan Tanggung Jawab Sosial terhadap Kinerja Keuangan dengan Feminisme Dewan Direksi sebagai Variabel Moderasi - Sejati, Fajar Rina; Zakaria, Zakaria; Aidha, Nur (Jurnal Ilmiah Akuntansi, 2020)
This study aims to examine the effect of environmental performance and disclosure of corporate social responsibility on financial performance as moderated by board feminisme. The research sample is a manufacturing company listed on the Indonesia Stock Exchange and also included in the PROPER category for the 2013-2017 period. Sampling using purposive sampling technique, 8 companies were selected as samples, with the number of research data is 40. Data were analyzed using the MRA (Moderated Regression Analysis) method. The results of the study found that environmental performance has a positive effect on financial performance and corporate social responsibility disclosure has no effect on financial performance. Meanwhile, board feminisme weakens the relationship between environmental performance and financial performance, on the other hand, board feminisme strengthens the relationship between corporate social responsibility disclosure and financial performance.